Strategi Pengembangan Wana Wisata Kampoeng Ciherang dalam Meningkatkan Pendapatan Masyarakat (Studi Kasus di Desa Cijambu Kecamatan Tanjungsari Kabupaten Sumedang) - Ramdan, Mochamad; Sujaya, Dedi Herdiansah; Sukmawati, Dety; Oktaviani, Viona (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The Indonesian tourism industry is one of the government's priority programs to improve because tourism has a significant impact on the economy. This research is needed to (1) Find out how the community's income varies around Kampoeng Ciherang tourism (2) Knowing how to measure and analyze the Kampoeng Ciherang tourist attraction development strategy in increasing community income in Cijambu Village, Tanjungsari District, Sumedang Regency. The research population is the people of Cijambu Village, Tourism Managers and Tourists. Sampling was carried out purposively. The research method used in this research is the case study method. The technical analysis used is descriptive analysis with a qualitative approach. Analysis of the data used uses SWOT. Based on the research results, it was concluded that the average income of people selling around Kampoeng Ciherang was IDR. 300,000-500,000. Strategies that can be implemented are (1) Utilizing existing natural potential to empower local communities by making special foods or souvenirs (2) Adding and improving supporting facilities as well as developing and adding interesting and varied rides & photo spots (3) Collaborating with investors to promote tourism and develop concepts tourism by prioritizing elements of local wisdom and upholding uniqueness and attractiveness